Analisis Pengaruh Pendapatan Perkapita dan Inflasi terhadap Industri Jasa Perhotelan di Indonesia - Sunarto, Robbi; Aqualdo, Nobel (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research was conducted by analyzing data on the number of Indonesian guest star hotels in Indonesia, per capita income data, and inflation data. This study aims to determine how the effects of inflation on income per capita and the number of Indonesian guest star hotels in Indonesia from 2003 to 2012. The data used are secondary data are time series for 10 years, and method of data analysis used in this study is the Ordinary Last Square (OLS) multiple linear regression model to calculate the tool eviews program. From the calculation results were obtained coefficient value of each independent variable is X1 (per capita income) amounted to 0.000549, meaning that if there is an increase per capita income by 1% then the number of Indonesian guests at five-star hotel 0.549000 0rang increased. Furthermore, the value of coefficient X2 (inflation) is -93.06227, meaning that in the event of a rise in inflation by 1% then the number of Indonesian guests at five-star hotel to experience the loss of 93062.27. In this study also tested the level of a significant level of 95% (α = 0.05%), then the calculation results obtained from probabiliti for revenue of 0.0000, and the inflation of 0.4549. It can be seen that the per capita income have a significant effect in influencing the number of Indonesian guests at five-star hotel, because probabiliti for per capita income is less than α = 0.05, whereas inflation does not significantly influence the number of guests at five-star hotel premises it is characterized by probabiliti for inflation greater than α = 0.05. Indonesia change the number of guests at five-star hotel is able to simultaneously explained by per capita income variables (X1) and inflais (X2) is 94,27persen, while the remaining 5.73 percent is explained by other factors that are not included in the model used in this research.Keywords: Earnings of perkapita, Inflation, Amount Of Guest Indonesia [At] Hotel have Star.